2021
DOI: 10.1140/epjc/s10052-021-09777-3
|View full text |Cite
|
Sign up to set email alerts
|

Z lepton flavour violation as a probe for new physics at future $$e^+e^-$$ colliders

Abstract: In this work we assess the potential of discovering new physics by searching for lepton-flavour-violating (LFV) decays of the Z boson, $$Z\rightarrow \ell _i \ell _j$$ Z → ℓ i ℓ j , at the proposed circular $$e^+e^-$$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…While finalizing our paper we notice ref. [87] on arXiv which presented a study of the LFV decays through Z-flavour violation in the context of future colliders. The discussion on the LFV decays partly overlaps with the present work.…”
Section: Jhep01(2022)107mentioning
confidence: 99%
“…While finalizing our paper we notice ref. [87] on arXiv which presented a study of the LFV decays through Z-flavour violation in the context of future colliders. The discussion on the LFV decays partly overlaps with the present work.…”
Section: Jhep01(2022)107mentioning
confidence: 99%
“…The flavor changing Z decays for example currently constrain |X | 10 −3 . In the future Tera Z factories are expected to reach a sensitivity similar of low energy CLFV observables [61] in the channels Z → τ . Lepton flavor universality violation tests are already considered in the fit of ref.…”
Section: Jhep03(2022)010mentioning
confidence: 99%
“…Here, we note that nonzero µ e implies some other nonzero µ i to satisfy the conservation of hypercharge, which is implicitly taken into account in Eqs. ( 14) to (16). In this case, the electron charge is converted to q ∆ f as described by the above transport equations.…”
Section: Transport Equations With Lfv Interactionsmentioning
confidence: 99%
“…Also, the discovery of neutrino oscillations revealed that the lepton flavor symmetries, U (1) L e −L µ × U (1) L µ −L τ , are violated [6-10], which further implies the violation of U (1) B −L if neutrinos are Majorana fermions [11]. However, such interactions are so feeble that they could be inefficient up to T B −L ∼ 10 13 GeV, depending on possible UV completions of the neutrino sector.Charged-lepton flavor violation (CLFV) is currently attracting a lot of attention [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], since its discovery would undoubtedly imply physics beyond the SM (plus massive neutrinos), enabling us to probe new physics at extremely high energy scales, such as O 10 8 GeV by µ → eγ [13] and O 10 9 GeV by µ → ea, where a is a pseudo-Nambu-Goldstone boson like an axion or familon [22,28]. 1 This is because CLFV induced by the SM neutrino masses is extremely suppressed by the GIM mechanism [49].…”
mentioning
confidence: 99%
See 1 more Smart Citation